(untitled) (Indian Journal of Veterinary Pathology, 2025)
A total of 120 fallen ruminants (64 cattle, 09 buffaloes, 15 sheep and 32 goats), received for necropsy at the Division of Pathology, ICAR-IVRI, Izatnagar were included in the study. Among animals, higher mortality rate was observed in adult animals followed by 3 to 12 months old animals and young animals upto 3 months age. In the present study was conducted to assess the types of pneumonia in ruminants based on gross and histopathological findings. Further, C categorization of pneumonia was primarily based on histopathology finding of the lung tissue. Tissue sections were stained with special stains such as Periodic Acid Schiff (PAS), Masson Trichrome Stain (MTS) and Brown and Brenn (B&B) respectively for demonstration of goblet cell hyperplasia, fibrous tissue proliferation and bacteria, respectively. Histopathological examination of lungs tissue sections was carried out for 120/123 cases as due to autolytic changes in 3 cases. Histopathological examination revealed one or more lesions associated with pneumonia in 97.56% (120/123) cases. Bronchointerstitial pneumonia 65.831% (79/120) was the most common type followed by interstitial (16.66%, 20/120), bronchopneumonia 7.5% (9/120) and granulomatous pneumonia (0.83%, 1/120). Bronchointerstitial pneumonia included chronic (1.66%, 2/120), sub-acute (55.83%, 67/120) and acute forms (8.33%, 10/120). Interstitial pneumonia (16.66%, 20/120) was sub categorized into acute (4.16%, 5/120) and subacute interstitial pneumonia (12.5%, 15/120). The lesions of bronchopneumonia was diagnosed in 7.5% (9/120) animals, which included acute (0.83%, 1/120), fibrinous (0.83%, 1/120) and subacute bronchopneumonia 5.83% (7/120) and granulomatous pneumonia (0.83%, 1/120). Besides, miscellaneous conditions were diagnosed in 9.16% (11/120) animals, which included congestion and edema in 6/120 (5%) and emphysema in 5/120 (4.16%) cases. Other miscellaneous conditions like congestion, edema, emphysema, atelectasis, etc. were observed in 9.16% (11/120) animals.